The effects of prone position ventilation in patients with acute respiratory distress syndrome. A systematic review and metaanalysis (2015)
Introduction: Prone position ventilation has been shown to improve oxygenation and ventilatory mechanics in patients with acute respiratory distress syndrome. We evaluated whether prone ventilation reduces the risk of mortality in adult patients with acute respiratory distress syndrome versus supine ventilation.Methodology: A metaanalysis of randomized controlled trials comparing patients in supine versus prone position was performed. A search was conducted of the Pubmed, Embase, Cochrane Library, and LILACS databases. Mortality, hospital length of stay, days of mechanical ventilation and adverse effects were evaluated.Results: Seven randomized controlled trials (2,119 patients) were included in the analysis. The prone position showed a nonsignificant tendency to reduce mortality (OR: 0.76; 95%CI: 0.54 to 1.06; P=.11, I-2 63%). When stratified by subgroups, a significant decrease was seen in the risk of mortality in patients ventilated with low tidal volume (OR: 0.58; 95%CI: 0.38 to 0.87; P=.009, I-2 33%), prolonged pronation (OR: 0.6; 95%CI: 0.43 to 0.83; p = .002, I-2 27%), start within the first 48 hours of disease evolution (OR 0.49; 95%CI 0.35 to 0.68; P=.0001, I-2 0%) and severe hypoxemia (OR: 0.51: 95%Cl: 0.36 to 1.25; P=.0001, 12 0%). Adverse effects associated with pronation were the development of pressure ulcers and endotracheal tube obstruction.Conclusions: Prone position ventilation is a safe strategy and reduces mortality in patients with severely impaired oxygenation. It should be started early, for prolonged periods, and should be associated to a protective ventilation strategy. (C) 2014 Elsevier Espana, S.L.U. and SEMICYUC. All rights reserved.